Developing Fuzzy-Promethee Method by using AHP Method on Student Achieving Selection - Rina Widyasari; Hendra Cipta; Abdul Halim Hasugian (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2020)
The achievements are the result of a person doing. Achievement can be achieved by relying on intellectual ability, emotional, and spiritual and resilience in the face of situations in all aspects of life. Student achievement awards can be either scholarship or involve the student in the national and international mathematics Olympiad. In UINSU, determining the best students in each major still uses manual procedures. Promethee is a method to resolve decision-making cases that belong to the MCDM with the outranking principle. This research developed a decision support system that involves AHP and Fuzzy-Promethee. The result shows the model that integrating AHP and Fuzzy-Promethee, which criteria in achievement selected by AHP, then the value of each criterion enter fuzzification, select the best student by Promethee method.